Preparation method of positive electrode material for improving low-temperature performance of LFP battery

Modified lithium iron phosphate was prepared by blending lithium iron phosphate, Ti3C2Tx and Bi2Te3 and mixing it with binder and conductive agent, which solved the problem of lower conductivity and ion diffusion rate of LFP batteries in low temperature environments, and achieved Significant improvement in battery performance.

CN119447257APending Publication Date: 2025-02-14YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411649416.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The conductivity and ion diffusion rate of LFP batteries in low temperature environments significantly reduce, resulting in a decrease in battery capacity and cycling performance, affecting its scope of application and performance.

Method used

Modified lithium iron phosphate is prepared by blending lithium iron phosphate, Ti3C2Tx and thermoelectric material Bi2Te3 and sintering it, and mixing it with a binder and a conductive agent to prepare a positive electrode material that improves the low-temperature performance of LFP batteries.

Benefits of technology

This method effectively improves the conductivity and flame retardant performance of LFP batteries at low temperatures, extends the service life of the battery and improves the range.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a preparation method of a positive electrode material for improving the low-temperature performance of an LFP battery. The modified lithium iron phosphate is prepared by adding lithium iron phosphate, flame-retardant modified Ti < 3 > C < 2 > T < x > and a thermoelectric material Bi < 2 > Te < 3 >. And mixing the modified lithium iron phosphate, a binder and a conductive agent to prepare the positive electrode material. The positive electrode material has high conductivity, flame retardance and good low-temperature performance, so that the positive electrode material has a wide application prospect in the technical field of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for preparing a positive electrode material for improving the low-temperature performance of an LFP battery. Background Art

[0002] As the world pays more attention to environmental friendliness and sustainable development, China has actively responded to the "dual carbon" goal and vigorously promoted the development of the new energy industry. Lithium iron phosphate (LFP) batteries are widely used in electric vehicles and other fields due to their low cost, environmental protection and high safety.

[0003] Improved low-temperature performance is particularly critical to improving the applicability and performance of batteries. The conductivity and ion diffusion rate of LFP materials drop significantly in low-temperature environments, resulting in a significant reduction in battery capacity and cycle performance. Improving low-temperature performance can be achieved through a variety of methods, such as material doping, structural optimization, and surface modification. These methods can improve the diffusion rate of ions in the material and reduce the impedance of the electrode reaction, thereby maintaining a high discharge capacity and long cycle stability in a low-temperature environment. Especially when used in northern regions or in winter, good low-temperature performance can significantly extend the service life of the battery and increase the range.

[0004] Electrical conductivity is one of the important indicators of positive electrode materials. Good electrical conductivity can ensure the efficient transmission of electrons during the charging and discharging process of the battery, reduce energy loss, and thus improve the overall performance of the battery. For LFP materials, the improvement of electrical conductivity can reduce the AC resistance of the battery and reduce the energy loss caused by internal resistance, which not only helps to increase the output power of the battery, but also prolong the service life of the battery. Especially in the scenario of rapid charging and discharging, excellent electrical conductivity can reduce battery heating and electrode polarization, thereby improving the performance and cycle stability of the battery.

[0005] Flame retardancy is crucial to battery safety. During use, batteries may overheat or short-circuit due to various factors, causing fire risks. The flame retardancy of LFP materials can be improved by adding flame retardants or other modification methods, thereby reducing the possibility of battery fire. Especially in high-energy density applications such as large-scale energy storage systems and electric vehicles, the improvement of flame retardancy can effectively ensure the safety of equipment and personnel and avoid huge losses caused by fire accidents.

[0006] In order to overcome the defects of the prior art, the present invention provides a method for preparing a positive electrode material for improving the low temperature performance of an LFP battery. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a positive electrode material for improving the low temperature performance of an LFP battery, so as to solve the problems in the prior art.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] A positive electrode material for improving the low temperature performance of an LFP battery, comprising modified lithium iron phosphate, a binder and a conductive agent; wherein the modified lithium iron phosphate is composed of lithium iron phosphate, Ti3C2T x It is made by mixing with thermoelectric material Bi2Te3 and then sintering.

[0010] More optimally, the mass ratio of modified lithium iron phosphate, binder and conductive agent is (97-98):2:1; lithium iron phosphate and Ti3C2T x The mass ratio of is (100-105):1, the mass ratio of lithium iron phosphate to the thermoelectric material Bi2Te3 is (80-85):1; the binder is polyvinylidene fluoride, and the conductive agent is Super P.

[0011] More optimally, Ti3C2T x After modification, the specific preparation steps are:

[0012] S1: Ti3C2T x Add to deionized water and disperse evenly by ultrasonic to obtain Ti3C2T x solution; dissolving 5-aminoisophthalic acid in N,N-dimethylformamide to obtain a 5-aminoisophthalic acid solution; dissolving cobalt acetate tetrahydrate in deionized water to obtain a cobalt acetate tetrahydrate solution; adding the cobalt acetate tetrahydrate solution to Ti3C2T x After stirring evenly, add 5-aminoisophthalic acid solution and continue stirring for 40-60 minutes. After stirring, perform hydrothermal reaction at 85-90℃ for 24-30 hours. After the reaction, centrifuge and freeze-dry to obtain composite conductive Ti3C2T x ;

[0013] S2: Composite conductive Ti3C2T x The mixture was mixed with an ammonia solution with a pH of 9-10, ultrasonically dispersed for 1-2 hours, centrifuged and the upper suspension was collected, and the suspension was hydrothermally reacted at 70-75°C for 4-6 hours. After the reaction, the suspension was centrifuged and freeze-dried to obtain an amino-modified composite conductive Ti3C2T x ; Flame-retardant graphene oxide and amino-composite conductive Ti3C2T x Add to deionized water, ultrasonically disperse for 1-2h, filter and vacuum dry to obtain flame retardant modified Ti3C2T x .

[0014] More optimally, in step S1, Ti3C2T x The reaction mass ratio of 5-aminoisophthalic acid and cobalt acetate tetrahydrate is (0.3-0.4):0.14:0.19.

[0015] More optimally, in step S2, flame retardant graphene oxide and amino composite conductive Ti3C2T x The reaction mass ratio is 1:(1.0-1.2).

[0016] More optimally, the preparation process of flame-retardant graphene oxide is as follows: dispersing graphene oxide in deionized water to obtain a graphene oxide solution; mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and deionized water to obtain a magnesium aluminum salt solution; dropping the magnesium aluminum salt solution into the graphene oxide solution, and adjusting the pH to 9-11 with a sodium hydroxide solution, and then keeping it warm at 75-80°C for 10-12 hours. After the reaction is completed, cooling, centrifugal washing, and freeze-drying are performed to obtain hydrotalcite-modified graphene oxide; adding a polyethyleneimine aqueous solution and an activation solution to the hydrotalcite-modified graphene oxide aqueous solution, fully stirring for 25-30 hours, and after the stirring is completed, dialyzing to remove impurities and drying are performed to obtain flame-retardant graphene oxide.

[0017] More optimally, the reaction mass ratio of graphene oxide, magnesium nitrate hexahydrate, and aluminum nitrate nonahydrate is (0.10-0.15):1:0.5.

[0018] More optimally, the concentration of the hydrotalcite-modified graphene aqueous solution is 1.0-1.2 mg / mL, the concentration of the polyethyleneimine aqueous solution is 10-15 mg / mL, and the concentration of the activation solution is 12-15 mg / mL; the reaction volume ratio of the polyethyleneimine aqueous solution, the activation solution, and the hydrotalcite-modified graphene aqueous solution is 1:1:1; the activation solution includes 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide, wherein the reaction mass ratio of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide is (1.0-1.5):5.

[0019] The method for preparing a positive electrode material for improving the low temperature performance of an LFP battery comprises the following steps: x After being mechanically mixed evenly with the thermoelectric material Bi2Te3, the modified lithium iron phosphate is obtained by high-temperature sintering; the modified lithium iron phosphate, polyvinylidene fluoride and Super P are mixed, coated on the surface of aluminum foil after mixing evenly, and vacuum dried to obtain the positive electrode material.

[0020] More optimally, the high temperature sintering parameters are: 800-850°C sintering for 10-12h, a heating rate of 40-50°C / min, and an annealing rate of 15-20°C / min.

[0021] Beneficial effects of the present invention:

[0022] The present invention is characterized in that by adding Ti3C2T x5-aminoisophthalic acid and cobalt acetate tetrahydrate were used to prepare a composite conductive Ti3C2T x This step is done by x On the one hand, MOF can effectively improve the Ti3C2T x The stacking and agglomeration problem of Ti3C2T x The conductive properties of conductive materials; on the other hand, the introduction of MOF can provide a rich pore structure to promote the diffusion of lithium ions and improve the conductive properties.

[0023] Furthermore, by adding ammonia solution, the composite conductive Ti3C2T x Amino groups are introduced into the surface of Ti3C2T, and then the abundant oxygen-containing groups on the surface of flame-retardant graphene oxide are combined with amino groups to form a flame-retardant graphene oxide. x The flame retardant components are introduced to effectively improve the Ti3C2T x The flame retardant properties of Ti3C2T x . The preparation principle of flame-retardant graphene oxide in this step is: by adding graphene oxide, magnesium nitrate hexahydrate, and aluminum nitrate nonahydrate, a hydrotalcite-modified graphene oxide is prepared; further, by adding a polyethyleneimine aqueous solution and reacting with the carboxyl groups on the surface of the hydrotalcite-modified graphene oxide to generate amide bonds, flame-retardant graphene oxide is obtained. The flame-retardant graphene oxide achieves the synergistic effect of multiple flame-retardant mechanisms through the heat absorption, film formation and gas dilution effects of hydrotalcite, the carbonization and gas-phase flame retardancy of polyethyleneimine, and the physical barrier effect of graphene oxide. This enables the material to effectively inhibit combustion, reduce heat release and flame spread when subjected to high temperature or flame, and exhibit excellent flame-retardant properties.

[0024] In summary, the highly conductive Ti3C2T x Hole injection can be formed, thereby increasing the carrier concentration of the matrix, thereby reducing the resistance of lithium iron phosphate and indirectly improving its cycle performance; in addition, Ti3C2T x The flame retardant components can also significantly improve the flame retardancy of the positive electrode material. The doping of the thermoelectric material Bi2Te3 can increase the interface thermal resistance of the matrix, thereby greatly reducing the lattice thermal conductivity, and ultimately achieve comprehensive regulation of heat and electrical transport, optimize the thermoelectric performance, and thus improve the low-temperature performance. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Source of raw materials:

[0027] Ti3C2T x , provided by Forsman Technology (Beijing) Co., Ltd., model 2203054; graphene oxide, particle size 35000 mesh; polyethyleneimine, provided by Hubei Watson Chemical Technology Co., Ltd., with an active ingredient content of 99%; polyvinylidene fluoride, provided by Dongguan Hongta Plastic Co., Ltd., model KF850 powder.

[0028] Example 1: LiFePO4 and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is (100-105):1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is (80-85):1

[0029] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 103:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 83:1.

[0030] Example 2: It is basically the same as Example 1, except that lithium iron phosphate and Ti3C2T x The mass ratio is (90-95):1

[0031] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 93:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 83:1.

[0032] Example 3: It is basically the same as Example 1, except that lithium iron phosphate and Ti3C2T x The mass ratio is (95-100):1

[0033] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 97:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 83:1.

[0034] Example 4: It is basically the same as Example 1, except that: lithium iron phosphate and Ti3C2T x The mass ratio is (105-110):1

[0035] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 107:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 83:1.

[0036] Example 5: It is basically the same as Example 1, except that lithium iron phosphate and Ti3C2T x The mass ratio is (110-115):1

[0037] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 113:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 83:1.

[0038] Example 6: The same as Example 1, except that the mass ratio of lithium iron phosphate to the thermoelectric material Bi2Te3 is (70-75): 1

[0039] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 103:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 73:1.

[0040] Example 7: The same as Example 1, except that the mass ratio of lithium iron phosphate to the thermoelectric material Bi2Te3 is (75-80): 1

[0041] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 103:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 77:1.

[0042] Example 8: It is basically the same as Example 1, except that the mass ratio of lithium iron phosphate to the thermoelectric material Bi2Te3 is (85-90):1

[0043] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 103:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 87:1.

[0044] Example 9: is basically the same as Example 1, except that the mass ratio of lithium iron phosphate to the thermoelectric material Bi2Te3 is (90-95):1

[0045] Step 1: LiFePO4, Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3, the modified lithium iron phosphate was obtained by sintering at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min. The modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed and coated on the surface of aluminum foil after mixing evenly. The positive electrode material was obtained by vacuum drying. The mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1. The mass ratio of lithium iron phosphate and Ti3C2T x The mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 103:1, and the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 93:1.

[0046] Example 10: Lithium iron phosphate material and flame retardant modified Ti3C2T x The mass ratio of the materials is (100-105):1, and the mass ratio of the lithium iron phosphate material to the thermoelectric material Bi2Te3 is (80-85):1

[0047] Step 1: Ti3C2T x The material was added into deionized water and ultrasonically dispersed to obtain Ti3C2T x solution; dissolving 5-aminoisophthalic acid in N,N-dimethylformamide to obtain a 5-aminoisophthalic acid solution; dissolving cobalt acetate tetrahydrate in deionized water to obtain a cobalt acetate tetrahydrate solution; adding the cobalt acetate tetrahydrate solution to Ti3C2T x The solution was stirred evenly, and then 5-aminoisophthalic acid solution was added and stirred for 60 min. After the stirring was completed, the mixture was subjected to hydrothermal reaction at 90 °C for 30 h. After the reaction was completed, the composite conductive Ti3C2T was obtained by centrifugation and freeze-drying. x Material: Ti3C2T x The reaction mass ratio of materials, 5-aminoisophthalic acid and cobalt acetate tetrahydrate is 0.3:0.14:0.19;

[0048] Step 2: Composite conductive Ti3C2T x The material was mixed with an ammonia solution with a pH of 9, ultrasonically dispersed for 1 h, and then centrifuged and the upper suspension was collected. The suspension was hydrothermally reacted at 75 ° C for 6 h. After the reaction, it was centrifuged and freeze-dried to obtain the amino-modified composite conductive Ti3C2T x Material;

[0049] Step 3: Disperse graphene oxide in deionized water to obtain a graphene oxide solution; mix magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and deionized water to obtain a magnesium aluminum salt solution; add the magnesium aluminum salt solution dropwise to the graphene oxide solution, adjust the pH to 9 with a sodium hydroxide solution, and then keep it at 80°C for 12 hours. After the reaction is completed, cool, centrifuge and wash, and freeze-dry to obtain hydrotalcite-modified graphene oxide; add 10 mg / mL of polyethyleneimine aqueous solution and 12 mg / mL of activation solution to 1 mg / mL of hydrotalcite-modified graphene oxide aqueous solution, and stir until the mixture is completely dissolved. The mixture was stirred for 30 hours, and after the stirring was completed, the mixture was dialyzed to remove impurities and dried to obtain flame-retardant graphene oxide; the reaction mass ratio of graphene oxide, magnesium nitrate hexahydrate, and aluminum nitrate nonahydrate was 0.12:1:0.5; the reaction volume ratio of polyethyleneimine aqueous solution, activation solution, and hydrotalcite-modified graphene aqueous solution was 1:1:1; the activation solution included 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide, wherein the reaction mass ratio of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide was 1:5;

[0050] Step 4: Flame retardant graphene oxide and amino composite conductive Ti3C2T x The material was added to deionized water, ultrasonically dispersed for 1 h, filtered and vacuum dried to obtain flame retardant modified Ti3C2T x Materials: Flame-retardant graphene oxide and amino-composite conductive Ti3C2T x The reaction mass ratio of the materials is 1:1;

[0051] Step 5: Lithium iron phosphate material and flame retardant modified Ti3C2T x The material and the thermoelectric material Bi2Te3 were mechanically mixed uniformly, sintered at 800℃ for 10h, with a heating rate of 40℃ / min and an annealing rate of 15℃ / min to obtain a modified lithium iron phosphate material; the modified lithium iron phosphate material, polyvinylidene fluoride and Super P were mixed, coated on the surface of aluminum foil after mixing uniformly, and vacuum dried to obtain a positive electrode material; the mass ratio of the modified lithium iron phosphate material, polyvinylidene fluoride and Super P was 97:2:1; the lithium iron phosphate material and the flame retardant modified Ti3C2T x The mass ratio of the materials is 103:1, and the mass ratio of the lithium iron phosphate material to the thermoelectric material Bi2Te3 is 83:1.

[0052] Comparative Example 1: basically the same as Example 1, except that: no Ti3C2T x Introduction

[0053] Step 1: After mechanically mixing lithium iron phosphate and thermoelectric material Bi2Te3 evenly, sinter at 800°C for 10 hours, with a heating rate of 40°C / min and an annealing rate of 15°C / min to obtain modified lithium iron phosphate; mix the modified lithium iron phosphate, polyvinylidene fluoride and Super P, coat them on the surface of aluminum foil after mixing evenly, and obtain the positive electrode material after vacuum drying; the mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P is 97:2:1; the mass ratio of lithium iron phosphate to thermoelectric material Bi2Te3 is 83:1.

[0054] Comparative Example 2: basically the same as Example 1, except that no thermoelectric material Bi2Te3 is introduced

[0055] Step 1: LiFePO4, Ti3C2T x After mechanical mixing, the modified lithium iron phosphate was sintered at 800°C for 10 hours, the heating rate was 40°C / min, and the annealing rate was 15°C / min to obtain the modified lithium iron phosphate; the modified lithium iron phosphate, polyvinylidene fluoride and Super P were mixed, coated on the surface of aluminum foil after mixing evenly, and vacuum dried to obtain the positive electrode material; the mass ratio of modified lithium iron phosphate, polyvinylidene fluoride and Super P was 97:2:1; lithium iron phosphate and Ti3C2T x The mass ratio is 103:1.

[0056] Comparative Example 3: Basically the same as Example 1, except that lithium iron phosphate is directly used as the positive electrode material

[0057] Step 1: Mix lithium iron phosphate, polyvinylidene fluoride and Super P, coat them on the surface of aluminum foil after mixing evenly, and obtain the positive electrode material after vacuum drying; wherein the mass ratio of lithium iron phosphate, polyvinylidene fluoride and Super P is 97:2:1.

[0058] Detection test:

[0059] Test of low temperature cycle performance: The positive electrode material prepared by the present invention is used as a raw material, and in an argon atmosphere, a battery is assembled in the following order: button battery shell, positive electrode material, dripping electrolyte, placing diaphragm, dripping electrolyte, placing lithium sheet, placing gasket shrapnel, button battery shell. At a low temperature of -20°C, a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A) is used to perform 10, 30, and 50 cycles of 0.2C charge and discharge tests on the battery, and the voltage range is 2.0-3.5V.

[0060] Flame retardant performance test: The positive electrode material prepared by the present invention was used as a sample, and the sample size was 130mm×6.5mm×3.2mm. According to the ASTM D2863 standard, the LOI value of the sample was measured using the LOI901 limiting oxygen index (LOT) tester of the German NetzschTaums Instrument Company. All samples were tested 5 times, and the arithmetic average of the results was taken. The results are as follows:

[0061] 10-cycle performance 30-cycle performance 50-cycle performance Oxygen index / % Example 1 95.3% 92.1% 87.4% 23.5 Example 2 92.1% 89.1% 83.1% 23.4 Example 3 92.5% 89.5% 83.3% 23.5 Example 4 92.9% 90.4% 83.7% 23.4 Example 5 92.4% 89.5% 83.1% 23.5 Example 6 91.6% 88.8% 82.8% 23.5 Example 7 91.7% 89.2% 83.3% 23.5 Example 8 91.1% 89.3% 82.8% 23.4 Example 9 91.0% 88.8% 81.3% 23.4 Example 10 97.4% 94.5% 90.2% 31.7 Comparative Example 1 89.1% 84.9% 79.2% 23.1 Comparative Example 2 86.3% 82.1% 77.7% 23.5 Comparative Example 3 80.1% 73.4% 65.1% 22.9

[0062] Conclusion: Through the data analysis of Examples 2-5, it can be seen that when lithium iron phosphate and Ti3C2T x When the reaction mass ratio is not within the ratio (100-105):1, the low temperature cycle performance of the battery will be reduced. x The low temperature cycle performance of the battery will be significantly reduced. Through the data analysis of Examples 6-9, it can be seen that when the reaction mass ratio of lithium iron phosphate to the thermoelectric material Bi2Te3 is not within the ratio (80-85): 1, the low temperature cycle performance of the battery will be reduced. Furthermore, when the thermoelectric material Bi2Te3 is not added in Comparative Examples 2 and 3, the low temperature cycle performance of the battery will be significantly reduced. In summary, lithium iron phosphate and Ti3C2T x The optimal reaction mass ratio of is (100-105):1, and the optimal reaction mass ratio of lithium iron phosphate and thermoelectric material Bi2Te3 is (80-85):1.

[0063] In addition, by analyzing the data of Example 10 and other examples, it can be seen that: x After modification, the low temperature cycle performance and oxygen index of the battery are improved. Therefore, the modification treatment of the present invention can effectively improve the performance of Ti3C2T x Flame retardant and conductive properties.

[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0065] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive electrode material for improving the low temperature performance of LFP batteries, characterized in that: It includes modified lithium iron phosphate, a binder and a conductive agent; wherein the modified lithium iron phosphate is composed of lithium iron phosphate, Ti3C2T x It is made by mixing with thermoelectric material Bi2Te3 and then sintering.

2. The positive electrode material for improving the low temperature performance of LFP battery according to claim 1, characterized in that: The mass ratio of modified lithium iron phosphate, binder and conductive agent is (97-98):2:1; lithium iron phosphate and Ti3C2T x The mass ratio of is (100-105):1, the mass ratio of lithium iron phosphate to the thermoelectric material Bi2Te3 is (80-85):1; the binder is polyvinylidene fluoride, and the conductive agent is Super P.

3. The positive electrode material for improving the low temperature performance of LFP battery according to claim 1, characterized in that: Ti3C2T x After modification, the specific preparation steps are: S1: Ti3C2T x Add to deionized water and disperse evenly by ultrasonic to obtain Ti3C2T x solution; dissolving 5-aminoisophthalic acid in N,N-dimethylformamide to obtain a 5-aminoisophthalic acid solution; Dissolve cobalt acetate tetrahydrate in deionized water to obtain a cobalt acetate tetrahydrate solution; add the cobalt acetate tetrahydrate solution to Ti3C2T x After stirring evenly, add 5-aminoisophthalic acid solution and continue stirring for 40-60 minutes. After stirring, perform hydrothermal reaction at 85-90℃ for 24-30 hours. After the reaction, centrifuge and freeze-dry to obtain composite conductive Ti3C2T x ; S2: Composite conductive Ti3C2T x The mixture was mixed with an ammonia solution with a pH of 9-10, ultrasonically dispersed for 1-2 hours, centrifuged and the upper suspension was collected, and the suspension was hydrothermally reacted at 70-75°C for 4-6 hours. After the reaction, the suspension was centrifuged and freeze-dried to obtain an amino-modified composite conductive Ti3C2T x ; Flame-retardant graphene oxide and amino-composite conductive Ti3C2T x Add to deionized water, ultrasonically disperse for 1-2h, filter and vacuum dry to obtain flame retardant modified Ti3C2T x .

4. The positive electrode material for improving the low temperature performance of LFP battery according to claim 3, characterized in that: In step S1, Ti3C2T x The reaction mass ratio of 5-aminoisophthalic acid and cobalt acetate tetrahydrate is (0.3-0.4):0.14:0.

19.

5. The positive electrode material for improving the low temperature performance of LFP battery according to claim 3, characterized in that: In step S2, flame retardant graphene oxide and amino-composite conductive Ti3C2T x The reaction mass ratio is 1:(1.0-1.2).

6. The positive electrode material for improving the low temperature performance of LFP battery according to claim 5, characterized in that: The preparation process of flame-retardant graphene oxide is as follows: dispersing graphene oxide in deionized water to obtain a graphene oxide solution; mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and deionized water to obtain a magnesium aluminum salt solution; dropping the magnesium aluminum salt solution into the graphene oxide solution, adjusting the pH to 9-11 with a sodium hydroxide solution, and then keeping the temperature at 75-80°C for 10-12 hours, cooling, centrifugal washing, and freeze-drying after the reaction is completed to obtain hydrotalcite-modified graphene oxide; adding a polyethyleneimine aqueous solution and an activation solution into the hydrotalcite-modified graphene oxide aqueous solution, fully stirring for 25-30 hours, and after the stirring is completed, dialyzing to remove impurities and drying to obtain flame-retardant graphene oxide.

7. The positive electrode material for improving the low temperature performance of LFP battery according to claim 6, characterized in that: The reaction mass ratio of graphene oxide, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate is (0.10-0.15):1:0.5; the concentration of the hydrotalcite-modified graphene aqueous solution is 1.0-1.2 mg / mL, the concentration of the polyethyleneimine aqueous solution is 10-15 mg / mL, and the concentration of the activation solution is 12-15 mg / mL.

8. The method for preparing a positive electrode material for improving the low temperature performance of an LFP battery according to claim 1, characterized in that: The following steps are involved: Lithium iron phosphate and flame retardant modified Ti3C2T x After being mechanically mixed with the thermoelectric material Bi2Te3 and sintered at high temperature, modified lithium iron phosphate is obtained; The modified lithium iron phosphate, polyvinylidene fluoride and Super P are mixed, coated on the surface of aluminum foil after mixing evenly, and vacuum dried to obtain a positive electrode material.

9. The method for preparing a positive electrode material for improving the low temperature performance of an LFP battery according to claim 8, characterized in that: High temperature sintering parameters: 800-850℃ sintering for 10-12h, heating rate of 40-50℃ / min, annealing rate of 15-20℃ / min.

10. A battery prepared according to the positive electrode material according to any one of claims 1 to 7.